Solar Charger Design for Electric Vehicles (International Journal of Innovative Research in Computer Science & Technology, 2022)
As countries and car makers focus on  goals like "going green," combating climate change, and  so on, the present worldwide trend toward electric vehicles  is expanding. The design of electric vehicles is an  important aspect of this. Electric cars are powered by  electricity generated by a power source, most often  batteries. These batteries require charging. A charging  station must be supplied for this reason. The charging  stations or points transform the energy they have access to  from a variety of sources into DC electrical energy for the  automobile. These devices had to be willing to handle  human input, namely the amount of power to be used, in  order for the user to pay for what they need. In this paper,  an electric car is charged using a local bank capacity, a PV Powerwall is available. This simulation sets the foundation  for solar-powered electric vehicle (EV) charger designs.
Keywords: Electric Vehicles; Charging Station; DC; Batteries